Social behaviour in farm animals [ - Gonyou, H. W. [ (Harold W.)]; Keeling L. J. [ (Linda J.)] (CABI Publishing, 2001)
An understanding of social behaviour is increasingly necessary in farm animal husbandry as more animals are housed in groups rather than in individual stalls or pens. There may be economic or welfare reasons for such housing. This book specifically addrsses this subject.